2001
DOI: 10.1021/jp012138p
|View full text |Cite
|
Sign up to set email alerts
|

Organometallic Complexes for Nonlinear Optics. 24. Reversible Electrochemical Switching of Nonlinear Absorption

Abstract: The molecular inorganic compounds 1,3,5-{trans-[RuCl(dppe)2]C⋮C-4-C6H4C⋮C}3C6H3 (1), trans-[Ru(C⋮C-4-C6H4C⋮CPh)Cl(dppe)2] (2), and trans-[Ru(C⋮CPh)Cl(dppm)2] (3) exhibit reversible oxidation in solution, assigned to the metal-centered RuII/III processes. Complexes 1−3 are essentially transparent at frequencies below 20 × 103 cm-1, whereas the green complexes 1 + −3 + have a strong absorption band centered near 11−12 × 103 cm-1. These absorption bands have been utilized to dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
85
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 110 publications
(92 citation statements)
references
References 13 publications
7
85
0
Order By: Relevance
“…The vinylidene salt 5 was then deprotonated to yield the tris-alkynyl complex trans, trans,trans-[{(dppe) 2 ClRu(CϵC-4-C 6 H 4 )} 3 N] (6); complex 6 had previously been prepared from tris(4-ethynylphenyl)-amine and 1 without isolation of the trivinylidene complex. [16] There was no difference in the reactivity of 5 or 6 towards ethynylferrocene, both of which afforded trans, trans,trans-[{(η 5 [17] All complexes were characterized by IR and 1 H and 31 P NMR spectroscopy, high-resolution mass spectrometry, and satisfactory microanalyses; the structures of complexes 2 (Figure 1), 3 (Figure 2), and 4 ( Figure 3) were confirmed by single-crystal X-ray diffraction studies. The IR spectra of the alkynyl complexes contain a ν CϵC band at around 2060 cm -1 due to the metal-bonded alkynyl group, whereas the spectra of the vinylidene complexes show a ν C=C band at around 1630 cm -1 together with a strong band at 839 cm -1 that corresponds to the PF 6 -counterion.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The vinylidene salt 5 was then deprotonated to yield the tris-alkynyl complex trans, trans,trans-[{(dppe) 2 ClRu(CϵC-4-C 6 H 4 )} 3 N] (6); complex 6 had previously been prepared from tris(4-ethynylphenyl)-amine and 1 without isolation of the trivinylidene complex. [16] There was no difference in the reactivity of 5 or 6 towards ethynylferrocene, both of which afforded trans, trans,trans-[{(η 5 [17] All complexes were characterized by IR and 1 H and 31 P NMR spectroscopy, high-resolution mass spectrometry, and satisfactory microanalyses; the structures of complexes 2 (Figure 1), 3 (Figure 2), and 4 ( Figure 3) were confirmed by single-crystal X-ray diffraction studies. The IR spectra of the alkynyl complexes contain a ν CϵC band at around 2060 cm -1 due to the metal-bonded alkynyl group, whereas the spectra of the vinylidene complexes show a ν C=C band at around 1630 cm -1 together with a strong band at 839 cm -1 that corresponds to the PF 6 -counterion.…”
Section: Resultsmentioning
confidence: 99%
“…Theoretical Methods: Density functional theory calculations were executed in this study using the Amsterdam Density Functional (ADF) program, version ADF 2010.01, [55] developed by Baerends et al [56,57] Calculations were performed in parallel mode with the VAYU supercomputer housed at the ANU Supercomputer Facility and operated under the National Computational Infrastructure Scheme. Calculations in C s symmetry were pursued on the structure [trans-(η 5 In all calculations and for all atoms, the all-electron Slater-type orbital basis sets used were of triple-ζ-plus-polarization quality (TZP). Geometry optimizations employed the gradient algorithm of Versluis and Ziegler.…”
Section: -Ethynyl-nn-diphenylanilinementioning
confidence: 99%
See 1 more Smart Citation
“…Alkynylmetal complexes constitute a particularly important class of organometallic complexes with p-conjugated bridges both on account of their intrinsic interest and, more recently, their potential as components or models of nanoscale electronic [16][17][18] and optical devices [19][20][21][22][23][24][25], related to the fact that the metal atom lies in the same plane as the p-system and can participate to the extension of the pconjugated path. From a design perspective, the metal acetylide linkage is appealing because of the rigid nature of the alkyne ligands and the defined directionality in the case of trans substituted metal centers [26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…This observation is consistent with the previous study of 1 a, which revealed a very weak communication between the various metallic centers connected by this type of central organic core. [15,16] Spectroelectrochemistry: Once the oxidation potentials were known, the oxidized states of these compounds could be readily generated in situ by using an optically transparent thin-layer electrochemical (OTTLE) cell. The optical properties of 2, 3-H, 3-NO 2 , and 4, and of their oxidized states were thus investigated by UV/Vis/NIR spectroelectrochemistry ( Figure 1).…”
mentioning
confidence: 99%